Quaternary Ammonium Ionic Liquid as a Dual Solvent-Catalyst in Biginelli Reaction - Tebabel, Imane; Boumoud, Taoues; Boumoud, Boudjemaa; Abdelmadjid, Debache (Letters in Organic Chemistry, 2016)
Multi-component reactions (MCRs) utilizing unconventional solvents like ionic liquids have become a new research direction that has emerged as an important facet of green chemistry. The present work deals constructively with the MC one pot synthesis of 4-aryl-5-ethoxycarbonyl-3,4-dihydro-6- methylpyrimidin-2(1H)-ones using L-valine sulfate 1:1 [H-Val][HSO4], a cheap, non-corrosive, and eco-friendly ionic liquid as a dual solvent-catalyst.
Keywords: Biginelli compounds